Insomnia, hypnotic use, and road collisions: a population-based, 5-year cohort study. Issue 8 (29th February 2020) - Morin, Charles M; Altena, Ellemarije; Ivers, Hans; Mérette, Chantal; LeBlanc, Mélanie; Savard, Josée; Philip, Pierre
Abstract: Study Objectives: The study objectives were to examine accidental risks associated with insomnia or hypnotic medications, and how these risk factors interact with sex and age. Methods: A population-based sample of 3, 413 adults ( M age = 49.0 years old; 61.5% female), with or without insomnia, were surveyed annually for five consecutive years about their sleep patterns, sleep medication usage, and road collisions. Results: There was a significant risk of reporting road collisions associated with insomnia (hazard ratio [HR] = 1.20; 95% confidence interval [CI] = 1.00–1.45) and daytime fatigue (HR = 1.21; 95% CI = 1.01–1.47). Insomnia and its daytime consequences were perceived to have played some contributory role in 40% of the reported collisions. Both chronic (HR = 1.50; 95% CI = 1.17–1.91) and regular use of sleep medications (HR = 1.58; 95% CI = 1.16–2.14) were associated with higher accidental risks, as well as being young female with insomnia and reporting excessive daytime sleepiness. Conclusions: Both insomnia and use of sleep medications are associated with significant risks of road collisions, possibly because of or in association with some of their residual daytime consequences (i.e. fatigue and poor concentration). The findings also highlight a new group of at-risk patients, i.e. young women reporting insomnia and excessive daytime sleepiness.